Reconceptualising Barriers to Engagement with Climate Change (Groundings Undergraduate, 2024)
This paper contributes to the discourse on climate change by emphasising the imperative for inclusive engagement, particularly at the intersection of socio-economic challenges and climate impacts in Glasgow, Scotland. Despite recent shifts towards a ‘Just Transition’ and increased public engagement efforts, working-class voices remain marginalised. To address this gap, the paper first reviews existing literature on Climate Change Communication (CCC), examining some of the competing conceptualisations of barriers and public engagement and their policy implications, and more specifically, participatory policymaking and its role in engagement. Through doing so, the central debates of how public engagement with climate change ought to be pursued will be established, and to what degree this can be understood in the context of developing engagement with working-class people. Subsequently, it proposes a novel framework synthesising insights from Lorenzoni, Sutton, and Tobin utilising an ecological Marxist perspective that aims to address barriers to climate change engagement among the working class.
Keywords: Climate Change; Communication; Public Engagement; Participatory policymaking; Policy; Discourse